Application of acid mine drainage for coagulation/flocculation of microalgal biomass. (June 2015) - Salama, El-Sayed; Kim, Jung Rae; Ji, Min-Kyu; Cho, Dong-Wan; Abou-Shanab, Reda A.I.; Kabra, Akhil N.; Jeon, Byong-Hun
Highlights: AMD contains high amount of Fe(II)/Al(III) ions which are natural flocculants. Sweeping microalgal floc formation was the dominant mechanism in this study. AMD can be an efficient coagulant/flocculant for low-cost microalgae harvesting. Abstract: A novel application of acid mine drainage (AMD) for biomass recovery of two morphologically different microalgae species with respect to AMD dosage, microalgal cell density and pH of medium was investigated. Optimal flocculation of Scenedesmus obliquus and Chlorella vulgaris occurred with 10% dosage of AMD at an initial pH 9 for both 0.5 and 1.0 g/L cell density. The flocculation efficiency was 89% for S . obliquus and 93% for C . vulgaris . Zeta potential (ZP) was increased from −10.66 to 1.77 and −13.19 to 1.33 for S . obliquus and C . vulgaris, respectively. Scanning electron microscope with energy-dispersive X-ray of the microalgae floc confirmed the sweeping floc formation mechanism upon the addition of AMD. Application of AMD for the recovery of microalgae biomass is a cost-effective method, which might further allow reuse of flocculated medium for algal cultivation, thereby contributing to the economic production of biofuel from microalgal biomass.